2020
DOI: 10.2196/preprints.18431
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Investigating the Accessibility of Voice Assistants With Impaired Users: Mixed Methods Study (Preprint)

Abstract: BACKGROUND Voice assistants allow users to control appliances and functions of a domotic house by simply uttering a few words. Such systems hold the potential to significantly help users with motor and cognitive disabilities who currently depend on their caregiver even for basic needs, e.g., opening a door. The research on voice assistants is mainly dedicated to abled-bodied users, and studies evaluating the accessibility of such systems are still sparse and fail to account for the part… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 29 publications
(34 reference statements)
0
5
0
Order By: Relevance
“…Voice assistant accessibility is therefore critical to ensure future systems are designed with the end user's interaction patterns and needs in mind (Ballati et al, 2018;Brewer et al, 2018;Addlesee, 2023). Industry voice assistants are created for the mass market (Masina et al, 2020), and today they are found in our homes, our cars, and many of our pockets (Ballati et al, 2018). They are trained on vast data sets to learn how to interact with the 'average user' , but speech production is nuanced, and not everyone perceives the world in the same way (Masina et al, 2020(Masina et al, , 2021Addlesee, 2023).…”
Section: Voice Assistant Accessibilitymentioning
confidence: 99%
See 3 more Smart Citations
“…Voice assistant accessibility is therefore critical to ensure future systems are designed with the end user's interaction patterns and needs in mind (Ballati et al, 2018;Brewer et al, 2018;Addlesee, 2023). Industry voice assistants are created for the mass market (Masina et al, 2020), and today they are found in our homes, our cars, and many of our pockets (Ballati et al, 2018). They are trained on vast data sets to learn how to interact with the 'average user' , but speech production is nuanced, and not everyone perceives the world in the same way (Masina et al, 2020(Masina et al, , 2021Addlesee, 2023).…”
Section: Voice Assistant Accessibilitymentioning
confidence: 99%
“…Industry voice assistants are created for the mass market (Masina et al, 2020), and today they are found in our homes, our cars, and many of our pockets (Ballati et al, 2018). They are trained on vast data sets to learn how to interact with the 'average user' , but speech production is nuanced, and not everyone perceives the world in the same way (Masina et al, 2020(Masina et al, , 2021Addlesee, 2023). For example, certain user groups-often those who can benefit the most from voice assistants-speak more disfluently than the average user (Addlesee et al, 2019;Masina et al, 2020;Ehghaghi et al, 2022).…”
Section: Voice Assistant Accessibilitymentioning
confidence: 99%
See 2 more Smart Citations
“…result of the same new age technology called AI. At the core, these assistants is a simple synchronous cycle includes Voice commands [4] and hear responses.…”
Section: Related Workmentioning
confidence: 99%